The care provided to families in the psychosocial care center: perceptions of professionals (Research, Society and Development, 2021)
The aim of this study is to identify the actions of health professionals regarding the care provided to family members of users of an Adult Psychosocial Care Center III. Method: Qualitative descriptive and exploratory research. Data collection was performed through recorded interviews, guided by a semi-structured questionnaire, applied to 28 professionals from a CAPSIII in the city of São Paulo. Data were processed by software. Results: From the analyzed corpus, six classes emerged that deal with the concept of family, the importance of care and bonding, in addition to the actions offered by the service to promote care for the family member. Conclusion: Professionals highlight the importance of being close to family members, which improves the treatment of users. Among the actions offered for family care are: family groups and home visits.